Different green manures showed inconsistent effects on soil properties, fungal communities and crop yield - Chenxin Wei; Zihan Hu; Yutong Jiang; Buyun Zhou; Zilong Hu; Guilong Li; Li Wan; Xingjia Xiang; Jia Liu (Journal of Soils and Sediments, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Interactions between plant growth and soil moisture determine the N2O source strength of farmed landscape depressions - Yujia Liu; Björn Kemmann; Per Ambus; Bo Elberling; Michael Dannenmann; Kristian Thorup-Kristensen; Daniel M. N. Poultney; Carsten W. Mueller (Plant and Soil, 2026)
Background Topographic depressions within agricultural fields contribute disproportionately to regional nitrous oxide (N 2 O) emissions. These low-lying areas accumulate nutrients and fine particles through water inflow and erosion, creating conditions conducive to elevated N 2 O emissions. Because depressions remain part of fields, understanding how crop presence and management influence their N 2 O source strength is essential. Methods A greenhouse mesocosm experiment was conducted using soil collected from an agricultural depression under either drained or partially waterlogged conditions (water table maintained 10 cm below the soil surface). Wheat was sown at three dates (57, 43, and 29 days before waterlogging) to represent different vegetative stages and capacities for N uptake. Dissolved organic carbon (DOC), dissolved nitrogen (N), root growth, and N 2 O emissions were continuously monitored. A 15 N-labelled fertilizer was applied during the waterlogging period to trace fertilizer-derived N in emitted N 2 O, soil, and plant biomass. Results Early-sown wheat was more strongly impaired by waterlogging than later-sown treatments but nevertheless significantly reduced N 2 O emissions compared with the unplanted control, irrespective of water regime. Early-sown plants also acted as stronger N sink, indicating that greater plant N acquisition contributed to reduced N availability for N 2 O production. In contrast, trends in DOC and cumulative N 2 O emissions across seeding dates were less consistent, particularly under waterlogged conditions. Conclusions Plant N uptake emerged as the primary mechanism reducing N 2 O emissions under the tested conditions. Although a general trend of lower N 2 O emissions with increasing plant age and N uptake was observed, the relationship was not strictly linear, due to plant age-specific interactions with waterlogging. Nevertheless, the results suggest that establishing crops in depression areas can mitigate N 2 O emissions by strengthening plant competition for available N, while the magnitude of this mitigation depends on both seeding date and waterlogging conditions.

Top-down trophic cascade effects on the restoration of ecological functions in heavy-metal-contaminated soils: Multi-trophic level regulation aggravates microbial metabolic limitation - Yanbin Du; Caihong Yu; Yuyan Zhu; Yijia Liu; Ying Shen; Rongrong Ma; Qiao Yang (Applied Soil Ecology, 2026)

Three decades of green manure rotations sustain soil nitrogen supply by microbial functional restructuring under reduced mineral fertilization - Lu Yang; Jia Liu; Junjie Huang; Zhan Jiang; Ming Liu; Weidong Cao (Applied Soil Ecology, 2026)

Effects of silver nanoparticles and nitrile fungicides on soil microbial community structure, metabolic functions, and resistance genes - Yiwang Wang; Ting Gao; Jiajia Liu; Shaoheng Bao; Fuli Wang; Ge Yao; Xiaoyan Lin; Shijie Jiang; Jinlong Lai; Penggang Han; Jiang Hui (Applied Soil Ecology, 2026)

Biodegradable microplastics increase fungi-mediated N2O emission by rapidly releasing dissolved organic matters - Lei Zhong; Yufeng Song; Xiaoxian Cai; Ping Wang; Guanqi Yu; Jia Liu; Xiaoxuan Su; Xingliang Xu (Applied Soil Ecology, 2025)

The microbial network exhibits higher complexity in the rhizosphere than in bulk soils along elevational gradients in the alpine forests - Dungang Wang; Shaojun Deng; Han Yang; Na Li; Qiuhong Feng; Jia Liu; Huajun Yin (Applied Soil Ecology, 2025)

Grazing exclusion changes the complexity and stability but not the α-diversity of the microbial community in a desert steppe - Fengqin Yuan; Xuebao Xu; Zhenpeng Liu; Rula Sa; Chongzhi Sun; Jia Liu; Na Li; Yujuan Zhang; Tongrui Zhang; Tingting Xing; Jie Ren; Shiming Tang; et al. (Applied Soil Ecology, 2025)

Green manuring increases network complexity and deterministic assembly of diazotrophic community in a subtropical paddy soil - Xianchu Su; Luyuan Sun; Yuntao Kang; Mengmeng Feng; Junkang Zhu; Anqi Wang; Zi-Yang He; Shengsheng Jin; Jia Liu; Ji-Zheng He; Yongxin Lin (Applied Soil Ecology, 2025)

Bacillus thuringiensis (Bt) rice straw mulching and earthworms mediated changes in soil N2O and CO2 emissions driven by N-cycling and C-utilizing microbial communities - Fuyuan Duan; Huiru Zhan; Shiqiang Ge; Zixuan Wang; Yangbeijia Liu; Zhenggao Xiao; Fengxiao Tan; Jianwu Wang; Yinghua Shu (Applied Soil Ecology, 2025)

Litter quality regulates cover crop litter decay alongside altered microbial facets - Guilong Li; Ke Leng; Wenjing Qin; Xiaofen Chen; Yongxin Lin; Ming Liu; Meng Wu; Jianbo Fan; Xiaoyue Wang; Yuji Jiang; Jia Liu (Applied Soil Ecology, 2024)